Creation of knowledge ‐ based economy in the European Union: The main typicalities and new ideas of clusterization - Melnikas, Borisas (Journal of Business Economics and Management, 2005)
Possibilities for the development of new forms of economic, social and technological headway designed to create and further improve economies based on knowledge are analyzed here. The main emphasis is put on national and regional economic specialization and creation of new networks of clusters in the situation of the development of the European Union. We have found that clusterization oriented towards the increase of efficiency of various national and regional economies is a critical precondition for successful creation of modern economy based on knowledge, both in the whole space of the European Union and particular countries. Another idea – a concept of creation of regional and cross‐regional clusters and their networks also known as “economic oazes”– is suggested here. It is explained in the paper that in the economies based on knowledge development of clusters and their networks will soon become one of the core forms of economic and technological advancement.First published online: 14 Oct 2010